Medical Students' Performances Using Different Assessment Methods during the Final Examination in Internal Medicine at the University of Benghazi, Libya - Buzaid, Najat; Lawgaly, Sami A.; Alawgali, Saleh M.; Albash, Amina; Alfakhri, Mousa (Libyan International Medical University Journal, 2023)
Background Distinctive evaluation tools assess diverse fields of learning that considerably impact the learning process.Objective To compare and correlate the performances of undergraduate final year medical students in written, clinical, and viva examinations in the subject of internal medicine.Methods This is a retrospective study. After authority approval, data was collected from final year examination results during 2019 to 2020. All the students of the medical school at University of Benghazi were included in this study. Their gender and their written, clinical, viva, and total scores were included. Data were coded and transferred from Excel to SPSS version 24 and expressed as frequencies and percentages. Chi-squared analysis was performed to test for differences in the proportions of categorical variables between two or more groups. Odd ratio (OR) is used to calculate the odds of passing the subject based on scores in different types of exams. Person's correlation (R) is used to evaluate the consistency of students' performances in different examinations. A p-value of less than 0.05 was considered the cut-off value of significant.Results The total number of students was 679, out of which 499 (73.5%) were females and 180 (26.5%) were males. The total number of students who passed the course was 422 (62%) with no significant differences between males and females. A statistically significant (p < 0.001) greater percentage of students achieved a passing score in clinical assessment (502 [73.9%]), followed by viva assessment (458.0 [67.5%]). The students performed the worse in written examination with only 291/679 (43%) students passing the examination, with no gender-based differences. There was a highly significant association between the total score of students who passed the subject and their scores in the written examination with an OR of 2.3 (p < 0.001). Viva examination and total score OR was 0.79 with no significant differences for males or females. On the contrary, there was a statistically significant negative association between clinical exams and total scores of students who passed the subject (OR = 0.58). There was a highly significant correlation (p < 0.001) between written examination and viva examination (R = 0.638), between written examination and clinical examination (R = 0.629), and between clinical and viva examinations (R = 0.763).Conclusion Students demonstrated higher performance on clinical and viva exams compared with written exams. Additionally, there were no notable disparities in results between male and female students across any of the three exam types. The written exam served as the most reliable indicator of a student's success in the subject. Furthermore, the data revealed a positive correlation between scores on the different exam formats, indicating that students exhibited consistent performance across all modes of evaluation.
Keywords: medical; performance; clinical examination; written examination; viva examination; internal medicine; Benghazi; Libya